2015
DOI: 10.1002/jssc.201500764
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted solid-phase extraction coupled with ultra high performance liquid chromatography and fluorescence detection for the determination of estrogens and their metabolites in wastewater

Abstract: Estrogens are an important class of endocrine-disrupting compounds, and their contamination of environmental waters through the effluents of wastewater treatment plants could have an important impact on aquatic biota, even at low concentrations. For this reason, the development of selective and sensitive extraction methodologies, which permit the identification and quantification of these compounds at trace level concentrations, is very important. In this study, a quantitative method based on molecularly impri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The recovery values for steroid hormones achieved in this study were in the range of 78.7–101.3%. According to the obtained results, it can be concluded that they were comparable and often better than those obtained in previous research in which MISPE was performed (60–105%) .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The recovery values for steroid hormones achieved in this study were in the range of 78.7–101.3%. According to the obtained results, it can be concluded that they were comparable and often better than those obtained in previous research in which MISPE was performed (60–105%) .…”
Section: Resultssupporting
confidence: 72%
“…There are several reports in the literature describing the usefulness of MIPs in the extraction of steroid hormones in water and wastewater samples. According to the data, MIPs were used for three estrogens (E2, E3, EE2) and two metabolites of E2 in wastewater samples, and the authors reported satisfactory recoveries above 60% and low RSDs under 10% . In another study, MIPs were used as a sorbent in extraction of E1, E2, and E3, and the achieved recoveries were in the range of 69–88% .…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation techniques such as LLE [28] and SPE [29,30] have been the standard methods for the extraction of analytes from aqueous samples; however, they require large volumes of organic solvents and time-consuming operation.…”
Section: Of Separation Sciencementioning
confidence: 99%
“…In this context, new sample preparation techniques have been developed over the past few years aiming at the reduction of solvent consumption (microextraction techniques) and replacement of toxic organic solvents (surfactants, nontoxic reagents, ionic liquids) . Sample preparation techniques such as LLE and SPE have been the standard methods for the extraction of analytes from aqueous samples; however, they require large volumes of organic solvents and time‐consuming operation. Recently, newly developed sample pretreatment methods, including cloud point extraction , stir bar sorptive extraction , membrane extraction , SPME , dispersive liquid‐phase microextraction , or dispersive liquid–liquid microextraction (DLLME) have been reported for detecting estrogens either in pharmaceutical formulations, food samples, environment matrices, or in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years (2015−2020), several kinds of commercial MIP cartridges were used for the SPE of analytes in various real samples [58–66]. These commercial MIP cartridges and their applications are listed in Table 1.…”
Section: New and Commercial Molecularly Imprinted Spe Adsorbentsmentioning
confidence: 99%